Pengaplikasian Metode Extreme Programming Pada Perancangan Sistem Informasi Berbasis Website - Yusran Panca Putra; Willi Novrian; Darmansah (STMIK Budi Darma, 2023)
Websites are often used to convey information from a company or other institution. The use of websites today is not only in education and government circles, but is evenly distributed in all business fields. The website has been used by MSMEs and other businesses to disseminate business information they have. It is recorded today that more than 1.9 billion websites use websites with various functions. Seeing this, PT. Yamaha Thambrin Panorama wants to take the opportunity to disseminate business information that is owned by creating a website-based information system. The business processes contained in PT. Yamaha Thambrin Panorama, namely selling motorcycles and workshops. In promoting products sold or managing data service and motorcycle spare parts, currently Information Technology services such as websites have not been maximized. Currently, the process is still using the conventional method, namely by distributing brochures and recording all transactions in the Microsoft Excel application. Based on the business processes that are currently running today, the researchers provide solutions that can help overcome the problems that have been described by designing an information system for PT. Website-based Yamaha Thambrin Panorama uses the Extreme Programming (XP) method. to ensure that all systems run as expected, the researcher uses the black box testing method. From the system that was built, it was found that all the features that were designed were running as expected